The Idea of Tolerance (a reading of its concept, limits, and dimensions) - Salman, Ihsan Abdulhadi (Journal of Legal and Political Studies, 2016)
The debate about the real world of freedom, often based on the idea of tolerance as a moral virtue. The principle of tolerance, one of the most important pillars of a democratic society, because of its concepts related to individual and collective liberties, and its association with the idea of fundamental human rights, and helps to respect the rights of others in order to coexist peacfully, as well as to achieve political and social stability. That tolerance means recognizing the multiplicity of cultures, and the culture of tolerance leading to building rules and laws of the civil state, as well as strengthening civil peace and integration, and acceptance of differences, through dialogue and mutuel understandig and acceptance of the other opinion.
Keywords: Tolerance; Freedom; Mora; Individual and Collective liberties; Human Rights; Civil Peace; Integration